Determinants of Care-Seeking Practices for Children with Sickle Cell Disease in Ekiti, Southwest Nigeria - Olatunya OS; Babatola AO; Adeniyi AT; Lawal OA; Daramola AO; Agbesanwa TA; Ojo TO; Ajayi PO; Ibijola AA; Komolafe AK; Adekile A (Journal of Blood Medicine, 2021)
Oladele Simeon Olatunya,1,2 Adefunke Olarinre Babatola,1,2 Adewuyi Temidayo Adeniyi,1,2 Olubunmi Adeola Lawal,3 Alaba Olanrewaju Daramola,4 Tosin Anthony Agbesanwa,5 Temitope Olumuyiwa Ojo,6 Paul Oladapo Ajayi,7 Adeleke Ajayi Ibijola,8 Akinwumi Kolawole Komolafe,2 Adekunle Adekile9 1Department of Paediatrics, College of Medicine, Ekiti State University, Ado Ekiti, Nigeria; 2Department of Paediatrics, Ekiti State University Teaching Hospital, Ado Ekiti, Nigeria; 3Department of Paediatrics, Federal Teaching Hospital, Ido Ekiti, Ekiti State, Nigeria; 4Department of Hematology and Blood Transfusion, Ekiti State University, Ado Ekiti, Ekiti State, Nigeria; 5Department of Family Medicine, College of Medicine, Ekiti State University, Ado Ekiti, Ekiti State, Nigeria; 6Department of Community Health, Obafemi Awolowo University Ile-Ife, Ile-Ife, Osun State, Nigeria; 7Department of Community Medicine, College of Medicine, Ekiti State University, Ado Ekiti, Ekiti State, Nigeria; 8Department of Hematology, Federal Teaching Hospital, Ido Ekiti/Afe Babaloa University, Ado Ekiti, Ekiti State, Nigeria; 9Department of Pediatrics, Faculty of Medicine, Kuwait University, Kuwait City, KuwaitCorrespondence: Oladele Simeon OlatunyaDepartment of Paediatrics, College of Medicine, Ekiti State University, Ado Ekiti, Ekiti State, NigeriaTel +2348038617705Email ladeletunya@yahoo.comBackground: Due to the chronic nature of sickle cell disease (SCD), affected individuals may seek help from diverse places thus raising the need to understand their health-seeking behavior (HSB) in order to design an appropriate management policy for them.Aim: The aim of this study was to evaluate the HSB among pediatric SCD patients relative to their non-SCD counterparts attending a tertiary facility in Southwest Nigeria and identified predictors of poor HSB among SCD patients.Methods: A total of 110 children with SCD were recruited and studied for their HSPs which were compared with 110 non-SCD patients with other chronic medical conditions. Questionnaires were used to obtain self-reported information on participants’ socio-demographic data and HSB. Logistic regression was used to determine the predictors of poor HSB among the SCD cohort.Results: More SCD patients received treatments at private hospitals, patent medicine stores and faith-based centers compared to their non-SCD counterparts (p=0.0052; 0.006; and 0.007), respectively. No difference was observed in the patronage of traditional care centres 10 (9.1%) vs 6 (5.5%). More SCD patients 61 (55.5%) vs 35 (31.8%) exhibited poor HSB (p=0.0004). SCD patients who were not enrolled on health insurance scheme were 18 times more likely to have poor HSB (OR=18.38, 95% CI (4.41– 76.57), p value= < 0.0001) while absence of VOC within the preceding year reduces the risk of poor HSB by 91.5% (OR=0.085, 95% CI (0.028– 0.258), p value= < 0.0001).Conclusion: SCD patients in the study locality had poor HSB. This raises the need for their education on proper HSB. More enrollment into health insurance scheme and the prevention of VOC will lessen the burden of poor HSB. The high patronage of non-hospital care facilities in this study raises the need for stakeholders to monitor activities and train the operators at these informal care centres.Keywords: sickle cell disease, health-seeking behavior, non-orthodox care, Nigeria